Biological control of Heterodera glycines by spore-forming plant growth-promoting rhizobacteria (PGPR) on soybean - Xiang, Ni; Lawrence, Kathy S.; Kloepper, Joseph W.; Donald, Patricia A.; McInroy, John A. (PloS one, 2017)
Heterodera glycines, the soybean cyst nematode, is the most economically important plant-parasitic nematode on soybean production in the U.S. The objectives of this study were to evaluate the potential of plant growth-promoting rhizobacteria (PGPR) strains for mortality of H. glycines J2 in vitro and for reducing nematode population density on soybean in greenhouse, microplot, and field trials. The major group causing mortality to H. glycines in vitro was the genus Bacillus that consisted of 92.6% of the total 663 PGPR strains evaluated. The subsequent greenhouse, microplot, and field trials indicated that B. velezensis strain Bve2 consistently reduced H. glycines cyst population density at 60 DAP. Bacillus mojavensis strain Bmo3 suppressed H. glycines cyst and total H. glycines population density under greenhouse conditions. Bacillus safensis strain Bsa27 and Mixture 1 (Bve2 + Bal13) reduced H. glycines cyst population density at 60 DAP in the field trials. Bacillus subtilis subsp. subtilis strains Bsssu2 and Bsssu3, and B. velezensis strain Bve12 increased early soybean growth including plant height and plant biomass in the greenhouse trials. Bacillus altitudinis strain Bal13 increased early plant growth on soybean in the greenhouse and microplot trials. Mixture 2 (Abamectin + Bve2 + Bal13) increased early plant growth in the microplot trials at 60 DAP, and also enhanced soybean yield at harvest in the field trials. These results demonstrated that individual PGPR strains and mixtures can reduce H. glycines population density in the greenhouse, microplot, and field conditions, and increased yield of soybean.